The Effect of Pipe Diameter and Valve Opening Variations on Osborne Reynolds Apparatus Test : Pengaruh Variasi Diameter Pipa dan Bukaan Katup pada Alat Uji Osborne Reynolds Apparatus - Aini Lostari; Moh. Agus Wahyudi; Indah Riani, Novi (Universitas Muhammadiyah Sidoarjo, 2023)
The Reynolds number is a dimensionless number which is obtained from the ratio of the density, flow velocity and cross-sectional area of ​​the fluid that passes through it. The Reynolds number is also a number used to determine flow characteristics in the form of laminar, transitional and turbulent flow. This research was conducted at the Basic Phenomenon Laboratory of Mechanical Engineering Study Program, Qomaruddin University using the Osborne Reynolds Apparatus test equipment by observing dyes flowing in a flowing fluid stream (water) so as to obtain the flow visualization. The pipe test section variations include 6 mm, 8 mm and 10 mm as well as variations in valve openings from 30°, 42°, 54°, 66°, 78° to 90°. Based on the research results, the lowest flow rate, flow velocity and Reynolds number were obtained for a 6 mm pipe for a 15o valve opening with respective values ​​of 3.71 x 10-6 m3/s, 0.131 m/s, 958.87 and flow visualization shown is laminar flow. While the highest value was obtained for a 10 mm pipe with a 90o valve opening, each value was 1.287 x 10-4 m3/s, 1.639 m/s, 19957.04, and the flow visualization shown was turbulent flow.